Contemporary Clinical Characteristics, Imaging, Management, and Surgical and Nonsurgical Outcomes of Adult Patients With Subaortic Stenosis - Ankit Agrawal; Aro Daniela Arockiam; Muhammad Majid; Ushasi Saraswati; Joseph El Dahdah; Sanya Chandna; Joseph Kassab; Michel Chedid El Helou; Rishabh Khurana; Tiffany Dong; Mustafa Atar; Elio Haroun; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Subaortic stenosis (SAS) is characterized by a fibromuscular membrane located just below the aortic valve, causing fixed outflow tract obstruction. There is a paucity of studies evaluating this condition. This cohort study reviewed the contemporary characteristics and outcomes of SAS in adult patients in a single large referral center. Methods and Results We retrospectively studied adult patients with SAS evaluated at our center during 2011 to 2022. The primary outcome was all‐cause mortality and heart failure hospitalizations during follow‐up, with secondary end points including recurrence of SAS and repeat surgery after initial SAS surgery. Among 484 patients with SAS, key characteristics included mean age 55±18 years, 67.5% female, left ventricular outflow tract peak velocity 352±140 cm/s and gradient 57±40 mm Hg, left ventricular ejection fraction 60%±14%, 54.8% had prior SAS surgery, and 45.1% had surgery during follow‐up. Over a median follow‐up of 5.5 (1.5–12.3) years, 11.5% (n=56) died, 6.8% (n=33) had heart failure hospitalizations, 8.0% (n=39) experienced SAS recurrence, and 14 (5.9%) underwent repeat SAS surgery. Multivariable analyses identified older age per 10‐years (hazard ratio [HR], 1.37 [95% CI, 1.12–1.68]) and baseline New York Heart Association class (HR, 2.48 [95% CI, 1.54–3.99]) to be statistically significantly associated with the primary end point; higher body mass index, New York Heart Association class, and peak left ventricular outflow tract gradient were also statistically significantly associated with SAS recurrence and redo surgery. Conclusions Almost half of patients with SAS had surgery in the past or during follow‐up, and a significant minority had mortality or morbidity events during follow‐up. Identified prognosticators warrant further research to guide management.